Determinants of coexistence of undernutrition and anemia among children aged 6–59 months in Nepal: Evidence from the 2022 Nepal Demographic and Health Survey - Bikram Adhikari; Biraj Neupane; Jessica Rice; Niharika Jha; Kajol Dahal; Parash Mani Sapkota; Archana Shrestha; Yu Jiang; Xinhua Yu (PLoS ONE, 2026)
Introduction Undernutrition and anemia among children aged 6–59 months are significant public health issues in developing countries like Nepal. The coexistence of these conditions impacts childhood development. This study aimed to determine the prevalence of undernutrition and anemia, assess their coexistence, and identify contributing factors among children aged 6–59 months in Nepal. Methods We conducted a secondary analysis using data from 2022 Nepal Demographic and Health Survey (NDHS 2022), a nationally representative cross-sectional survey. The outcome variables were undernutrition, anemia, and their coexistence. Undernutrition was defined as the presence of stunting, wasting, underweight, or any combination of these conditions. Anemia was defined as hemoglobin levels <11.0 g/dL (adjusted for altitude). We applied multivariable multinomial logistic regression to determine factors associated with coexistence, and multivariable logistic regression to assess factors associated with undernutrition and anemia separately. We presented the results from the regression analysis using adjusted odds ratio (aOR) and 95% confidence intervals (CI). Results Among 2,395 children, the weighted prevalence of undernutrition was 33.5%, anemia was 43.4%, and coexistence of undernutrition and anemia was 16.0%. Children from the richest wealth quintile, whose mothers had at least secondary education, and those whose mothers participated in household decision-making had 53% (aOR: 0.47; 95% CI: 0.26 to 0.86), 48% (aOR:0.52; 95% CI: 0.32 to 0.86), and 34% (aOR: 0.66; 95% CI: 0.47 to 0.94) lower odds of experiencing the coexistence of undernutrition and anemia compared to their counterparts. Children with underweight mothers had 80% (aOR:1.80; 95% CI:1.20 to 2.70) higher odds of coexistence compared to their counterparts. Conclusion The prevalence of undernutrition, anemia, and their coexistence among children was high in Nepal. Interventions that improve mothers’ education, strengthen their roles in the family, and enhance the household financial condition are essential to reduce these conditions and improve children’s nutritional status.